How To Measure Personal Financial Management Behavior During The Covid-19 Pandemic - Kadarningsih, Ana (Universitas Semarang, 2022)
This research was motivated by the existence of problems regarding the personal financial management behavior of the Students of the Faculty of Economics and Business Management Study Program at Dian Nuswantoro University Semarang (UDINUS) in 2021. This research was shown to examine financial literacy, financial attitudes, lifestyle and social environment on the personal financial management behavior of UDINUS students. This study amounted to 170 respondents using purposive sampling technique. Testing the data by doing classical assumption test, instrument test, multiple linear regression test and hypothesis testing with SPSS Version 23 analysis tool. The results of the study describe a positive and significant influence between financial literacy and financial management behavior in UDINUS students. Second result , there is a positive and significant relationship between financial attitudes and financial management behavior in UDINUS students. Third result is lifestyle does not have a positive effect on financial management behavior in UDINUS students. The last result is the social environment also have a positive and significantly effect on financial management behavior in UDINUS students.